(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Plantar fasciitis is a disorder in which there is non-inflammatory structural breakdown of the plantar fascia. It is more common in sports that involve running and long- distance walking. Many of the literature suggest that there is 21.7 % of prevalence rate of plantar fasciitis in individuals who play sports, especially in football players who uses studs/cleats shoes. Attachment of the cleats place the foot in a dorsiflexed position throughout the stance phase of running which produces and increases pressure upon the calcaneus. This creates a pull from soft tissue attachments such as plantar fascia which further leads to disorders like plantar fasciitis which needs to be treated early and by more advanced techniques to prevent further overuse injuries. Objective: To find the effect of conventional physiotherapy exercises versus kinesiotaping in football players with plantar fasciitis. Material and Method: In this pre-post intervention study 40 football players having plantar fasciitis were included. They were randomly divided into 2 groups with 20 individuals each. Group A was treated with conventional exercises and Group B with kinesiotaping along with conventional exercises for two weeks. After pre-post assessment, data was analysed with help of appropriate statistical methods. Results: According to the result, in Group A and Group B there is significant difference in pain and measures of foot function index with p value < 0.0001. Conclusion: The results obtained by studying both the groups in this study suggests that in treatment of plantar fasciitis, Conventional Therapy along with Kinesiotaping is more effective than Conventional Therapy alone.